Political Science Education in the Digital Age: Perspectives for Higher Education (Encuentros, 2024)
This paper starts from the task of finding pedagogical circuits that contribute to the improvement and innovation of pedagogical conditions that appeal to the latent potential of students. The question that serves as a beacon is: How are recent waves of change in the political and university arena shaping pedagogical strategies in political science, and what innovations could trigger an optimization of student training? Within this journey, the analysis flows into several estuaries: the current trends in political science education, the challenges that stand as hills in its university teaching, and the seismogram of technological innovations in political science pedagogy. At the same time, pedagogical strategies are outlined, and research tools are proposed as cartographies for political science education. In a last section, the knot of the political science curriculum in higher education is unraveled under the guidance of a qualitative methodology.
Keywords: Political science; Higher education; pedagogy; educational innovation; digital era